PIM findings influence the Punjab Agricultural Policy and the Pakistan National Food Security Policy - CGIAR Research Program on Policies, Institutions, and Markets (2018)
IFPRI/PIM contributed to two key policies adopted in 2018 in Pakistan: the Punjab Agricultural Policy, which lays out the province's framework for reform in agriculture, and the National Food Security Policy, which aims to eradicate hunger and malnutrition at the national level.